Performing history: culturally sustaining pedagogies for indigenous students in the historical disciplines. Issue 1 (2nd January 2021) - November, Nancy; Sturm, Sean; Wolfgramm-Foliaki, 'Ema
ABSTRACT: Current research into, and definitions of, historical literacy do not adequately acknowledge the cultural backgrounds of indigenous learners across the historical disciplines and levels. Nor do they recognise the vital role of historical literacy in empowering indigenous students. In conversations with teachers of a range of ethnicities and Māori and Pasifika students from across the historical disciplines, we asked: how can teachers inspire indigenous students to feel at home in the historical disciplines, do well in them and make them their own? The teachers and students saw historical literacy as predominantly textual in nature, and critical historical literacy as often culturally alien to Māori and Pasifika students. The teachers revealed that what worked to foster critical historical literacy in Māori and Pasifika students was multimodal performance. Accordingly, we argue that pedagogy in the historical disciplines that sustains Māori and Pasifika students culturally enables them to perform their culture through historical literacy – and, thus, to see history (both history per se and their histories) as open to their knowledge, critique and ownership.